Observations on Megaselia persecnt;ix (Diptera: Phoridae) in relation to its host Camponotus gigas (Hymenoptera: Formicidae) - Disney, R. H. L.; Maschwitz, U. (Malaysian Journal of Science, 1996)
The hitherto unknown male and egg of Megaselia persecutrix Schmitz are described. Observations on its oviposition attacks on its host ant Camponotus gigas (Latreille) are presented